2019
DOI: 10.3390/hydrology6010016
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Thermal Characteristics of Stormwater through Low Impact Development Systems

Abstract: Urbanization causes alteration of the thermal regime (surface, air, and water) of the environment. Heated stormwater runoff flows into lakes, streams, bays, and estuaries, which potentially increases the base temperature of the surface water. The amount of heat transferred, and the degree of thermal pollution is of great importance to the ecological integrity of receiving waters. This research reports on a controlled laboratory scale test to assess low impact development (LID) stormwater control measure impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The nonpoint source pollution reduction rate is 45.18%. LeBleu et al [21] The average leachate temperature in permeable paving is approximately 2 degrees Celsius lower than in pavement runoff.…”
Section: Seo Et Al [19]mentioning
confidence: 99%
See 1 more Smart Citation
“…The nonpoint source pollution reduction rate is 45.18%. LeBleu et al [21] The average leachate temperature in permeable paving is approximately 2 degrees Celsius lower than in pavement runoff.…”
Section: Seo Et Al [19]mentioning
confidence: 99%
“…For example, Glick et al [16], Abduljaleel et al [17], and Quichimbo-Miguitama et al [18] simulated the hydrological benefits in their study areas, among which Quichimbo-Miguitama also focused on the inundation reduction benefits; Seo et al [19] and Deng et al [20] conducted simulations to evaluate the hydrological and nonpoint source benefits in the study area. In regard to ecological improvement benefits, LeBleu et al [21] found that LID stormwater control measures would reduce the heat load of stormwater runoff and mitigate the urban heat island effect to some extent; Shen [22] simulated the heat island effect mitigation effect of green roofs; Lin et al [23] used the life cycle assessment method to quantify the carbon reduction in the study area. In cost-benefit research of grey and green infrastructure, Wilbers et al [24] divided the benefits of grey and green facilities into direct benefits (avoidance of sewage overflows and urban flooding) and co-benefits (aesthetic value, increase in house prices due to green roof installation, prevention of sewage disposal, water use, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In regard to ecological improvement benefits, LeBleu et al [21] found that LID stormwater control measures would reduce the heat load of stormwater runoff and mitigate the urban heat island effect to some extent. Shen [22] simulated the mitigation of the heat island effect by green roofs.…”
Section: Introductionmentioning
confidence: 99%
“…Stormwater carries pollutants and discharges them to surface waters. Pollutants include: Heavy metals (such as lead, zinc, copper, and cadmium), polycyclic aromatic hydrocarbons, soluble salts, pesticides, nitrogen, solids, pathogens, pharmaceuticals, and P. Phosphorus, a main pollutant in urban areas, enters waterways with surface water runoff degrading the waterways through over production of algae and aquatic plant growth [4][5][6][7][8][9][10][11]. The main source of urban P is residential lawns and streets.…”
Section: Introductionmentioning
confidence: 99%